1990
DOI: 10.1007/bf01735062
|View full text |Cite
|
Sign up to set email alerts
|

Muscle cramp: Main theories as to aetiology

Abstract: Historically relevant hypotheses on the pathophysiology of muscle cramp are reviewed. Psychosomatic, static, vascular, myogenic and neural theories are highlighted from a clinician's point of view. Modern neurophysiological research leaves little doubt that true muscle cramp is caused by explosive hyperactivity of motor nerves. Several mechanisms may be involved including spinal disinhibition, abnormal excitability of motor nerve terminals and spreading of muscle contraction by ephaptic transmission or axon re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 27 publications
0
30
1
Order By: Relevance
“…3 Prior neurophysiologic studies have shown that cramps arise from spontaneous discharges of motor nerves rather than from within the muscle itself. 10 It was speculated that decreased intravascular volume associated with hypoalbuminemia in liver disease results in increased muscle membrane hyperexcitability by lowering the "threshold frequency" required for the induction of a muscle cramp. In the current study, cirrhotic patients with cramps had significantly lower serum albumin levels, although the magnitude of difference (3.1 ± 0.6 g/dL vs 3.3 ± 0.7 g/dL) does not seem to be clinically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Prior neurophysiologic studies have shown that cramps arise from spontaneous discharges of motor nerves rather than from within the muscle itself. 10 It was speculated that decreased intravascular volume associated with hypoalbuminemia in liver disease results in increased muscle membrane hyperexcitability by lowering the "threshold frequency" required for the induction of a muscle cramp. In the current study, cirrhotic patients with cramps had significantly lower serum albumin levels, although the magnitude of difference (3.1 ± 0.6 g/dL vs 3.3 ± 0.7 g/dL) does not seem to be clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…10 Potential primary hypotheses include neurologic, muscular, endocrine, or electrolyte imbalance. 2,4,[9][10][11] Diuretic use in cirrhotic patients also has been implicated as a cause of muscle cramps through its effects on serum electrolyte balance and plasma volume. However, Abrams et al 2 found that patients with congestive heart failure had a lower prevalence of cramps compared with patients with cirrhosis despite higher diuretic use, suggesting that diuretic use may not be the primary precipitating factor for muscle cramps.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…D uring th e tre a tm e n t period, participants were randomly assigned 300 mg daily dose of hydroquinine hydrobromide dihydrate (54 participants) or placebo (58). The frequency, severity (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), duration, and location of muscle cramps, as well as any side-effects, were recorded by participants in daily diaries. The primary outcome measures were the number of muscle cramps and the number of days during which the participants had muscle cramps (cramp-days).…”
Section: Discussionmentioning
confidence: 99%
“…Increased sweat rate causes water and electrolyte losses, which leads to both dehydration and sodium depletion (Wexler, 2002). The primary concern with sodium losses in athletes is the resultant hyperexcitability of specific motor nerve endings due to mechanical stress and changes in surrounding electrolyte concentrations (Jansen, Joosten, & Vingerhoets, 1990;Layzer, 1994). Serum sodium concentrations were decreased in tennis (Bergeron, 2003a;Bergeron, 1996) and football players (Stofan et al, 2005) after exercising in the heat.…”
Section: Possible Mechanisms Contributing To Eamcmentioning
confidence: 99%